Patterns of diversity of the Monte Desert small mammals across multiple spatial scales - Rodriguez, Maria Daniela (2011)
The relationship between spatial scale and biodiversity patterns is a highly debated topic in ecology. We evaluated the partition of small mammal diversity at multiple spatial scales and analyzed protected areas in order to evaluate their role of protecting biodiversity at the regional scale. Diversity of small mammals in the Monte Desert was quantified at the regional biome scale (96,000 km2 ) (g) and partitioned at three spatial scales: aridity range (a3,n ¼ 6,16 000 km2 ), locality level (a2,n ¼ 18,2e3 ha), and habitat patch (a1,n ¼ 51,0.6 ha). We estimated their diversity using an additive approach with three indices (richness, Shannon-Weiner, Simpson). Diversity was higher than expected at the “between aridity range (b3)” scale, but lower at the “within-habitat scale (a1)”. Alpha was higher than beta diversity for most spatial scales; and at the regional scale protected areas preserved a higher biodiversity than unprotected ones. Our results are the first to partition the diversity of desert small mammals at multiple spatial scales and to support the hypotheses of an irregular scale dependence of alpha and beta diversity when increasing the spatial scales. They also highlight that a better understanding of biodiversity patterns is gained when several tools are integrated and combined at different spatial scales.